A repeated-measures assessment of golf shot performance at varying distances in collegiate female golfers using the TrackMan portable launch monitor - Fisher, K. (Journal of Advanced Sport Technology, 2019)
The Trackman portable launch monitor has become a popular tool of assessment and feedback among elite golfers, including tour professionals and U.S. collegiate teams. The device meets important criteria for assessing golf performance, including portability, accuracy, reliability, and instantaneous feedback. The goals of this study were to evaluate potential benefits of introducing the Trackman to a collegiate golf team and critically examine performance based on device data. In a pretest-posttest design, female collegiate golfers (n = 10) with an average handicap of six strokes were assessed on shot performance at varying distances at two different time points eight weeks apart using the Trackman "Combine" Standardized Test. Results indicated no significant interaction between the time point of assessment and shot distance (p = .625) and no significant main effect for time point (p = .995). However, there was a main effect for distance (p < .001), such that golfers struggled more with short and long shots when compared with those in the middle of the spectrum. Performance at the shortest yardage of 60 was significantly worse than 100 (p = .009), 120 (p = .019), and 140 yards (p = .047). Performance at longer distances of 160 and 180 yards was significantly worse than 100 (p = .020, p = .010, respectively) and 120 (p = .041, p = .020, respectively) yards, and driver performance was significantly worse than 80 (p = .001), 90 (p = .001), 100 (p < .001), 120 (p < .001), and 140 (p < .001) yards. These findings suggest that eight weeks of orientation and practice with such technology do not significantly alter baseline testing results regarding shot quality at varying goal distances. Furthermore, golfers in the current study comparably excel at golf shots of intermediate lengths (i.e., 80 - 140 yards) while demonstrating higher levels of variability outside this range. Implications for practice structure and performance are discussed.